Branching networks can have opposing influences on genetic variation in riverine metapopulations. Issue 12 (18th September 2020) - Chiu, Ming‐Chih; Li, Bin; Nukazawa, Kei; Resh, Vincent H.; Carvajal, Thaddeus; Watanabe, Kozo
Abstract: Aim: Fractal networks, represented by branching complexity in rivers, are ubiquitous in nature. In rivers, the number of either distal (e.g. in headwater streams) or confluent (e.g. in mainstems) locations can be increased along with their branching complexity. Distal‐ or confluent‐spatial locations can result in fewer or greater corridor linkages that can alter genetic divergence at the metapopulation scale. These mechanisms underlying the resulting genetic structuring remain poorly understood at the metapopulation scale, particularly in terms of the roles of species‐specific dispersal traits. The objective of this study was to mechanistically understand how branching complexity can simultaneously influence genetic divergence in opposite directions. Location: North‐eastern Japan. Methods: To evaluate the integrated influences of network complexity and species dispersal on genetic divergence among populations at the catchment scale, we modelled metapopulation genetic dynamics under a Bayesian inference framework by adapting empirical genetic data from four macroinvertebrate species. Simulations were then performed using empirical and virtual species characteristics on virtual river networks. Results: Our simulation experiments showed that both greater landscape connectivity (resulting from shorter watercourse distance) and greater isolation of distal locations occurred in the more‐branched river networks. These two spatial features have negative and positive influences on genetic divergence, with their relative importance varying among different species and dispersal characteristics. Specifically, genetic divergence at the metapopulation scale increased for species having higher downstream‐biased dispersal but decreased for species having higher upstream‐biased dispersal. Distal populations (e.g. in headwaters) have higher genetic independence when downstream‐biased asymmetry is higher. Main conclusions: We found a strong association between species dispersal and evolutionary processes such as gene flow and genetic drift. This association mediates the pervasive influences of branching complexity on genetic divergence in the metapopulation. It also highlights the importance of considering species dispersal patterns when developing management strategies in the face of rapid environmental change scenarios.